2014
DOI: 10.5812/jjhs.21718
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Removal From Drinking Water by Electrocoagulation Using Iron and Aluminum Electrodes

Abstract: Background: Existence of fluoride in drinking water above the permissible level causes human skeletal fluorosis. Objectives: Electrocoagulation by iron and aluminum electrodes was proposed for removing fluoride from drinking water. Materials and Methods: Effects of different operating conditions such as treatment time, initial pH, applied voltage, type and number of electrodes, the spaces between aluminum and iron electrodes, and energy consumption during electrocoagulation were investigated in the batch react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…All the chemicals were purchased from Merck company (Germany). The experimental stages were conducted at 30°C and the remained concentration of the metal was determined by atomic absorption spectrophotometer (PG model, England) (22). It is important to consider that all the experiments were replicated three times and the mean of data and the results were determined and used.…”
Section: The Preparation Of Synthetic Solutionsmentioning
confidence: 99%
“…All the chemicals were purchased from Merck company (Germany). The experimental stages were conducted at 30°C and the remained concentration of the metal was determined by atomic absorption spectrophotometer (PG model, England) (22). It is important to consider that all the experiments were replicated three times and the mean of data and the results were determined and used.…”
Section: The Preparation Of Synthetic Solutionsmentioning
confidence: 99%
“…Bazrafshan et al [38] determined that energy consumption was close to each other when using iron and aluminium electrodes for the same operating conditions. On the other hand, Takdastan et al [93] found that the iron electrode's energy consumption was almost quadruple as high as the aluminium electrode (5590 kwh kg −1 F − and 1435 kwh kg −1 F − , respectively) in the same conditions. Ün et al [56] concluded that increasing the time to 30 min and the current density to 3 mA cm 2 led to an increase in fluoride removal efficiency of up to 85.9% from water, which resulted further increase in the energy consumption of the process from 4 to 12.5 kWh m −3 .…”
Section: Energy Consumptionmentioning
confidence: 97%
“…For this reason, several researchers are moving toward combined EC processes to increase pollutants removal efficiency, such as fluoride found in drinking water. EC process can be used as a pre-or post-polishing process depending on the type of contaminants present in water [101][102][103][104][105].…”
Section: Integrated Ec Processes For Fluoride Removalmentioning
confidence: 99%
“…The photo-fenton oxidation process can be used as a suitable method for the removal of highly contaminated waters that contain large amounts of 3-Aminopyridine compound, and the removal rate can be augmented by increasing the reaction time (38). The fact that dye removal rates can be enhanced by increasing the reaction time (39) can be attributed to the high production of the OH°. Another study showed that the Fenton process was able to decolorize textile wastewater at 20 -40 minutes reaction time.…”
Section: )mentioning
confidence: 98%